Draft of a therapeutic, educational, and integration project for juveniles in Morocco (The International Journal for Scientific Research, 2025)
For me, the origin of my interest in the future and lives of juveniles in Morocco was not a coincidence. As a clinical psychologist and former executive with the General Delegation for Prison Administration, which I had the honor of joining for a long time, my role allowed me to observe the efforts made in this regard. Therefore, I believe that working on this issue is of great importance because of its psychological and social effects on the juvenile individual on the one hand, and also because of its solutions to the material and economic burdens on society. It is sufficient to refer to the statistics issued by official institutions to highlight the importance and necessity of deep contemplation and proactive prediction of this issue. Indeed, we find that even the efforts made by the supervisory sector clash with dishonest trends and positions in the search for reconciliation and integration into the fabric and values of society, whether on the part of the juveniles or their families. During the period of placement, which may not be less than 6 months, they are invited to a reformatory while enjoying a special system, different from the system for adults, and learning and training centers are provided to obtain a profession or trade upon their release. The fundamental paradox is that most detained juveniles do not engage seriously in vocational education and training centers. Rather, their involvement in these centers conceals a fundamental and specific background that is far removed from the aims and objectives of education and training, and the achievement of integration and harmonization with the goals and values of society. Evidence of this is the alarming and steady rise in recidivism rates. Therefore, we urgently need to reconsider the methods of dealing with and managing relationships with juveniles within correctional facilities, given the alarming rise in recidivism rates. This calls for a purely psychosocial perspective and treatment that restores the neglected role of the family, and fathers in particular
Keywords: Therapeutic Approach; System; Father Symbolism; Deviation